2018
DOI: 10.1002/ijc.31404
|View full text |Cite
|
Sign up to set email alerts
|

A PRDX1‐p38α heterodimer amplifies MET‐driven invasion of IDH‐wildtype and IDH‐mutant gliomas

Abstract: The Peroxiredoxin 1 (PRDX1) gene maps to chromosome arm 1p and is hemizygously deleted and epigenetically silenced in isocitrate dehydrogenase 1 or 2 (IDH)-mutant and 1p/19q-codeleted oligodendroglial tumors. In contrast, IDH-wildtype astrocytic gliomas including glioblastomas mostly lack epigenetic silencing and express PRDX1 protein. In our study, we investigated how PRDX1 contributes to the infiltrative growth of IDH-wildtype gliomas. Focusing on p38α-dependent pathways, we analyzed clinical data from 133 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…PRDX1 has been found to up-regulated in multiple cancer tissues. Previous studies have shown that PRDX1 facilitates the infiltrative growth of isocitrate dehydrogenase-wildtype gliomas by forming a heterodimer with p38α 24 . On the contrary, PRDX1 was also confirmed to be a tumor suppresser by protecting PTEN from oxidation-induced inactivation 22 .…”
Section: Discussionmentioning
confidence: 98%
“…PRDX1 has been found to up-regulated in multiple cancer tissues. Previous studies have shown that PRDX1 facilitates the infiltrative growth of isocitrate dehydrogenase-wildtype gliomas by forming a heterodimer with p38α 24 . On the contrary, PRDX1 was also confirmed to be a tumor suppresser by protecting PTEN from oxidation-induced inactivation 22 .…”
Section: Discussionmentioning
confidence: 98%
“…For example, the PRDX1 (Peroxiredoxin 1) this gene encodes a member of the peroxiredoxin family of antioxidant enzymes, which reduce hydrogen peroxide and alkyl hydroperoxides 14 . PRDX1 forms a heterodimer with p38α mitogen-activated protein kinase 14 (MAPK14), stabilizing phosphate-p38α in glioma cells 15 and epigenetic silencing of PRDX1 is frequent in 1p/19q-deleted oligodendroglial tumors and likely contributes to radio-and chemosensitivity of these tumours 16 ; XRCC5 (X-Ray Repair Cross Complementing 5) is the 80-kilodalton subunit of the Ku heterodimer protein, which is also known as ATP-dependant DNA helicase II or DNA repair protein XRCC5. The Polymorphisms of XRCC5 play an important role in astrocytoma prognosis in the Chinese Han population, which could be used in the determination of astrocytoma prognosis in clinical researches 17 ; BCL2L2 (BCL2 Like 2) is a member of the BCL-2 protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while ABL1 was found to be involved in DNA repair upon irradiation, thus contributing to radioresistance in GBM cells [32], a crucial role in linking RNA processing with signal transduction of ERK2 has recently been unveiled [33]. Moreover, activation of the MAPK14 signaling pathway has been previously shown to correlate with poor prognosis in GBM patients, increased tumor invasiveness and aggressive phenotype [34][35][36][37][38]. Here, in vitro kinase assays confirmed that MBZ could directly inhibit the kinase activity of these proteins, thus confirming their status of direct molecular targets of MBZ.…”
Section: Discussionmentioning
confidence: 99%